Penal Policy File No. 109. - Fowles, Tony; Wilson, David (Howard Journal of Criminal Justice, 2007)
The article reports on the penal policy file no.109. A Surveillance Society which was specially commissioned from the Surveillance Studies Network for the 28th International Data Protection and Privacy Commissioners' Conference and on the reports published by the Information Commissioner. The report describes a surveillance society as one where technology is routinely and extensively used to track and record our activities and movements.